The effect of the revision and implementation for environmental protection law on ambient air quality in China. (15th March 2022) - Yu, Chunling; Morotomi, Toru
Abstract: An unescapable fact is that air pollution has been a problem affecting residents' health and daily life. The Chinese government has been adopting measures to improve air quality for decades. The revise of Environmental Protection Law (the New Law hereafter) enforced in 2015 is one of them. The New Law encourages participations of multiple actors in environmental protection and aggressive punishments violations, playing the central role in the Chinese environmental law system. In order to understand its impacts, we employ the panel data analysis controlling city and month fixed terms to evaluate the effects of the New Law on air quality in 70 cities in China. Furthermore, we combine difference-in-differences (DID) to investigate the time variance of the effect. We find that the implementation of the New Law correlates with reduction of PM2.5, SO2 concentrations and Air Quality Comprehensive Index (AQCI). The effect is non-linear, reducing over time, especially on NO2 concentration and AQCI. In our model, one document reduces NO2 concentration and AQCI by 1.99 μg/m 3 and 0.26 points, and the effects decay by 0.93 μg/m3 and 0.16 every year separately. The results indicate the effectiveness of the New Law, while at the same time, China experiences symbolic implementations from local authorizations resulted from environmental decentralization, ambiguous policy statements and interest conflicts. Highlights: The implementation of revised Environmental Protection Law in China is examined to decrease PM2.5, SO2, concentrations and AQCI. The estimated effect of the implementation declines along time, especially for NO2 and AQCI. One document is associated with reduction of AQCI by 0.26 points, and the effects decay by 0.16 every year separately. Delays of responds from cities to central laws and symbolic implementation are recognized.